PENGUJIAN AIR LINDI TPA SAMPAH KOTA PALANGKA RAYA SEBAGAI PUPUK ORGANIK CAIR PADA TANAMAN OKRA: Testing Of Leachate In Municipal Solid Waste Landfill Palangka Raya As Liquid Organic Fertilizer On Okra Plant - Ruben Tinting Sirenden; Sulmin Gumiri; Bambang Supriono Lautt; Liswara Neneng (AgriPeat, 2022)
Okra Plant (AbelmoschusesculentusL. Moench) is a type of vegetable that is in high demand in Indonesia. Okra Fruit is not only known as vegetable but also known as a functional food because it contains fiber and secondary metabolites in the form of phenolic compound and flavonoid which are antioxidants which are useful for health. Okra plants can grow in a variety of soil types. One type of soil that can be found in the city of PalangkaRaya is podzols. Podzols is less productive is poor in nutrients, low Ph and porous so is easy to lose moisture and nutrient, therefore, inputs are needed, including fertilization. Liquid Organic fertilizer is a type of fertilizer that is being developed nowadays. This study aims to examine the effect of giving liquid organic fertilizer leachate from Palangka Raya Landfill to okra plants on podzols. The study was conducted in a green house and was arranged according to completely randomized design with leachate treatment from landfill, namely L0 (without treatment), L1 (150 ml plant-1), L2 (300 ml plant-1) dan L3 (450 ml plant-1). All treatments were repeated 6 times so which there were 24 experimental units. The results showed the administration of 450 ml of leachate showed the highest growth and yield of okra compared to other treatment, with height to 103cm, number of leaves 31 pieces, dry weight of stoves 576.89 g, and fresh weight of fruit 159.98 g